Children with autism spectrum disorder who improve with fever: Insights from the Simons Simplex Collection. Issue 1 (31st August 2017) - Grzadzinski, Rebecca; Lord, Catherine; Sanders, Stephan J.; Werling, Donna; Bal, Vanessa H.
Abstract : Literature indicates that some children with ASD may show behavioral improvements during fever; however, little is known about the behavioral profiles of these children. This study aims to (a) investigate the subset of children who show parent‐reported behavioral improvements associated with fever and (b) compare the demographic, behavioral, and genetic characteristics of this subset of children to children whose parents report no change during fever. Parents of 2, 152 children from the Simons Simplex Collection provided information about whether and in which areas their child improved during fever. Children were randomly assigned into discovery or replication samples. In discovery analyses, children who reportedly improved with fever (Improve Group) were compared to those who reportedly did not improve (No Improve Group) on demographics, medical history, ASD symptoms, adaptive skills, and presence of de novo ASD‐associated mutations. Significant and marginal results from discovery analyses were tested in the replication sample. Parent reports of 17% of children indicated improvements during fever across a range of domains. Discovery and replication analyses revealed that the Improve Group had significantly lower non‐verbal cognitive skills (NVIQ) and language levels and more repetitive behaviors. Groups did not differ on demographic variables, parent‐report of current ASD symptoms or the presence of de novo mutations. Understanding the profiles of children who improve during episodes of fever may provide insights into innovative treatments for ASD. Autism Res 2018, 11: 175–184 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: This study explored characteristics of children with ASD who are reported to improve during fever. Parents of 17% of children with ASD report improvements across a range of domains during fever including cognition, communication, repetitive behaviors, social interaction, and behavior. Children who are reported to improve during fever have significantly lower non‐verbal cognitive skills and language levels and more repetitive behaviors. Understanding the profiles of children who improve during episodes of fever may provide insights into new treatments for ASD.